2018
DOI: 10.1016/j.jbiomech.2017.11.019
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of patellofemoral cartilage morphology and deformation in anterior cruciate ligament deficient versus uninjured knees

Abstract: Anterior cruciate ligament (ACL) deficient patients have an increased rate of patellofemoral joint (PFJ) osteoarthritis (OA) as compared to the general population. Although the cause of post-injury OA is multi-factorial, alterations in joint biomechanics may predispose patients to cartilage degeneration. This study aimed to compare in vivo PFJ morphology and mechanics between ACL deficient and intact knees in subjects with unilateral ACL ruptures. Eight male subjects underwent baseline MRI scans of both knees.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 51 publications
(88 reference statements)
0
17
0
Order By: Relevance
“…A randomly selected knee from each subject (2 left, 5 right) was imaged first thing in the morning (8 AM) and again in the afternoon (4 PM) (Coleman et al, 2013; Widmyer et al, 2013) using a 3.0T MR scanner (Trio Tim; Siemens Medical Solutions; Malvern, PA) and an eight-channel knee coil (Invivo; Gainesville, FL) (Carter et al, 2015; Taylor et al, 2013; Utturkar et al, 2013). Subjects were asked to refrain from any strenuous weight-bearing activities 12 hours prior to the morning imaging session, and each subject rested supine for 45 minutes immediately before the baseline MR scan to enable cartilage equilibration (Eckstein et al, 1999; Owusu-Akyaw et al, 2018; Sutter et al, 2014). In order to most directly capture the effects of activities of daily living on T1rho relaxation times, no rest period was provided prior to the afternoon imaging session.…”
Section: Methodsmentioning
confidence: 99%
“…A randomly selected knee from each subject (2 left, 5 right) was imaged first thing in the morning (8 AM) and again in the afternoon (4 PM) (Coleman et al, 2013; Widmyer et al, 2013) using a 3.0T MR scanner (Trio Tim; Siemens Medical Solutions; Malvern, PA) and an eight-channel knee coil (Invivo; Gainesville, FL) (Carter et al, 2015; Taylor et al, 2013; Utturkar et al, 2013). Subjects were asked to refrain from any strenuous weight-bearing activities 12 hours prior to the morning imaging session, and each subject rested supine for 45 minutes immediately before the baseline MR scan to enable cartilage equilibration (Eckstein et al, 1999; Owusu-Akyaw et al, 2018; Sutter et al, 2014). In order to most directly capture the effects of activities of daily living on T1rho relaxation times, no rest period was provided prior to the afternoon imaging session.…”
Section: Methodsmentioning
confidence: 99%
“…This investigation quantified glenohumeral cartilage deformations in response to loaded exercise with previously validated MRI-based 3D solid modeling techniques. 8 , 9 , 15 , 16 , 24 , 29 , 32 Specifically, this study evaluated exercise-induced glenohumeral cartilage strain following a series of 30 push-ups. Compressive strains were measured in the glenoid (15%) and humeral head (17%) articular cartilage.…”
Section: Discussionmentioning
confidence: 99%
“…This method was previously validated and has been extensively used to quantify cartilage thickness in vivo in other joints. 8 , 9 , 15 , 16 , 24 , 29 , 32 Additionally, to ensure quality control, all segmentations were reviewed by a fellowship-trained musculoskeletal radiologist with 30 years of experience (C.E.S.). The bone and cartilage contours were then compiled to create a 3D surface mesh model of the humerus, the glenoid, and the respective cartilage surfaces (Geomagic Studio; Geomagic) ( Figure 1A ).…”
Section: Methodsmentioning
confidence: 99%
“…The double-echo steady-state sequence is like the previously described MERGE sequence in that it provides high-resolution contrast between bone and cartilaginous structures. 1,2,10 In their investigation, Schleich et al 9 found sensitivity, specificity, and accuracy of 98%, 76.2%, and 95.9%, respectively, for the detection of labral tears. A large part of what makes the study by Higashihira et al 4 unique, and ultimately compelling, is the description of labral tear frequency relative to acetabular location.…”
Section: See Related Article On Page 2857mentioning
confidence: 98%